Low density, good flowability cyclodextrin-raffinose binary carrier for dry powder inhaler: anti-hygroscopicity and aerosolization performance enhancement. (4th May 2018) - Zhao, Ziyu; Huang, Zhengwei; Zhang, Xuejuan; Huang, Ying; Cui, Yingtong; Ma, Cheng; Wang, Guanlin; Freeman, Tim; Lu, Xiang-yun; Pan, Xin; Wu, Chuanbin
ABSTRACT: Background : The hygroscopicity of raffinose carrier for dry powder inhaler (DPI) was the main obstacle for its further application. Hygroscopicity-induced agglomeration would cause deterioration of aerosolization performance of raffinose, undermining the delivery efficiency. Methods : Cyclodextrin-raffinose binary carriers (CRBCs) were produced by spray-drying so as to surmount the above issue. Physicochemical attributes and formation mechanism of CRBCs were explored in detail. The flow property of CRBCs was examined by FT4 Powder Rheometer. Hygroscopicity of CRBCs was elucidated by dynamic vapor sorption study. Aerosolization performance was evaluated by in vitro deposition profile and in vivo pharmacokinetic profile of CRBC based DPI formulations. Results : The optimal formulation of CRBC (R4 ) was proven to possess anti-hygroscopicity and aerosolization performance enhancement properties. Concisely, the moisture uptake of R4 was c.a. 5% which was far lower than spray-dried raffinose (R0, c.a. 65%). R4 exhibited a high fine particle fraction value of 70.56 ± 0.61% and it was 3.75-fold against R0 . The pulmonary and plasmatic bioavailability of R4 were significantly higher than R0 ( p  < 0.05). Conclusion : CRBC with anti-hygroscopicity and aerosolization performance enhancement properties was a promising approach for pulmonary drug delivery, which could provide new possibilities to the application of hygroscopic carriers for DPI.